Delaying bacillus Calmette-Guerin vaccination from birth to 4 1/2 months of age reduces postvaccination Th1 and IL-17 responses but leads to comparable mycobacterial responses at 9 months of age. - Burl, S; Adetifa, U; Cox, M; Touray, E; Ota, M; Marchant, A; Whittle, H; Mcshane, H; Rowland-Jones, S; Flanagan, K (2010)
Bacillus Camette-Guérin (BCG) vaccine is the only licensed vaccine against tuberculosis, yet its protective efficacy is highly variable between different geographical regions. We hypothesized that exposure to nontuberculous mycobacteria attenuates BCG immunogenicity by inducing mycobacterial-specific regulatory T cells (Tregs). Gambian neonates were recruited at birth and randomized to receive BCG vaccination either at birth or at 4 1/2 mo. Mycobacterial immune responses were assessed at birth, 4 1/2, and 9 mo of age. At 4 1/2 mo of age the BCG naive individuals had detectable mycobacterial responses, including increased IL-10 production suggesting environmental priming. Vaccination at birth significantly enhanced Th1, Th2, IL-6, IL-17, and Treg responses in mycobacterial cultures at 4 1/2 mo compared with the BCG naive group. Analyzing results at 4 1/2 mo postvaccination revealed lower IFN-gamma, IL-6, and IL-17 responses in the delayed BCG vaccine group compared with those vaccinated at birth, but this did not relate to Treg levels prevaccination. When comparing responses pre- and post-BCG vaccination in the delayed vaccine group, there was no priming of mycobacterial IL-17. Mycobacterial responses waned over 9 mo in those vaccinated at birth, leading to comparable mycobacterial immunity in both groups at 9 mo of age. Overall, these data suggest that vaccination at birth induces a broad Th1/Th2/IL-17/Treg mycobacterial response but the Th1/Th-17 response was reduced when delaying the vaccine. The evidence did not suggest that mycobacterial specific naturally occurring Tregs accounted for this attenuated immunogenicity.